Analysis of Fixed Asset Management in Improving Service Efficiency at Dr. H. Ibnu Sutowo General Hospital in Baturaja, Ogan Komering Ulu Regency, Oku Regency - Riadi Wijaya; Yunita Sari; Rini Efrianti (Institute for Law and Economics Studies, 2026)
This study aims to analyze the impact of fixed asset management and regulatory compliance on service efficiency at Dr. H. Ibnu Sutowo Baturaja Regional General Hospital in Ogan Komering Ulu Regency. Effective fixed asset management and regulatory compliance are key factors in supporting improvements in hospital service quality. This study employs a quantitative descriptive method with an explanatory research approach. The sampling technique uses a census method involving 47 respondents from the administration, finance, nursing logistics, and medical service logistics departments. Data collection was conducted through observation, interviews, questionnaires, and a literature review. Data analysis employed multiple linear regression, including validity and reliability testing, classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results of this study are expected to show that fixed asset management and regulatory compliance have a positive and significant effect on hospital service efficiency, both partially and simultaneously. Good asset management through optimal inventory, maintenance, and monitoring can improve the utilization of hospital resources, expedite services, and increase patient satisfaction. Furthermore, regulatory compliance supports the creation of effective, accountable hospital governance that meets healthcare service standards. Thus, this study is expected to serve as a basis for evaluation and recommendations for hospitals in improving the efficiency of healthcare services